Meningkatkan Hasil Belajar Dalam Materi Pecahan Melalui Bantuan Alat Peraga Benda Konkret - Yuliati Zebua (JURNAL GLOBAL EDUKASI, 2021)
Abstract: The purpose of this study was to improve learning outcomes in Class III-B semester I SD Negeri 070983 Sihare'o, Gunungsitoli Barat District, Gunungsitoli City, especially in fraction material through the help of concrete object props. The method in this research is a class research method. As for the research subjects, students of Class III-B SD Negeri 070983 Sihare'o semester I of Gunungsitoli Barat District, Gunungsitoli City in the academic year 2019/2020 consisted of 24 students, including 13 male students and 11 female students. The results of the study are as follows: In cycle I, 14 students (58.3%) completed their studies and 10 students (41.7%) who did not complete their studies with an average grade score of 6.2 and 61 absorption. 7%. The results in the second cycle of students who completed learning were 17 students (70.8%) and those who did not complete their studies were 7 students (29.2%) with an average grade score of 7.3 and absorption capacity of 73.3%. While the results in the third cycle the number of students who completed learning was 21 students (87.5%) and those who did not complete their studies were 3 (12.5%) students with an average grade score of 8.8 with absorption capacity of 87.9%. Because it had met the indicators of success and even exceeded the value that the researchers targeted, this research was stopped in cycle III. Keywords: props; concrete objects; fraction.  Abstrak: Tujuan penelitian ini adalah untuk meningkatkan hasil belajar pada siswa Kelas III-B semester I SD Negeri 070983 Sihare’o Kecamatan Gunungsitoli Barat Kota Gunungsitoli khususnya dalam materi pecahan melalui bantuan alat peraga benda konkret. Metode dalam penelitian ini adalah metode penelitian kelas. Adapun yang menjadi subjek penelitian adalah siswa Kelas III-B SD Negeri 070983 Sihare’o semester I Kecamatan Gunungsitoli Barat Kota Gunungsitoli tahun pelajaran 2019/2020 terdiri dari 24 siswa, diantaranya 13 siswa laki-laki dan 11 siswa perempuan. Hasil penelitian adalah sebagai berikut: Pada siklus I siswa yang tuntas belajar sejumlah 14 siswa (58,3 %) dan yang tidak tuntas belajar sejumlah 10 siswa (41,7 %) dengan nilai rata-rata kelas 6,2 dan daya serap 61,7 %. Hasil pada siklus II siswa yang tuntas belajar sejumlah 17 siswa (70,8 %) dan yang tidak tuntas belajar sejumlah 7 siswa (29,2 %) dengan nilai rata-rata kelas 7,3 dan daya serap 73,3 %. Sedangkan hasil pada siklus III jumlah siswa yang tuntas belajar 21 siswa (87,5 %) dan yang tidak tuntas belajar sejumlah 3 (12,5 %) siswa dengan nilai rata-rata kelas 8,8 dengan daya serap 87,9%. Karena sudah memenuhi indikator keberhasilan bahkan sampai melebihi dari nilai yang peneliti targetkan, maka penelitian ini dihentikan pada siklus III. Kata kunci: alat peraga; benda konkret; pecahan.